A call to action toward integrated testing and earlier care for viral hepatitis, HIV, STIs and TB - Raben, D (2020)
Objectives. The objective of the paper is to present the outcomes of the HepHIV 2019 conference, held in Bucharest under the Romanian EU Presidency and focusing on challenges of timely and integrated testing and care. Methods. The conference programme was put together by the organizing committee. It consisted of invited talks and peer-reviewed abstracts. Results. In all, 65 abstracts from 20 countries were presented during the conference, which had nearly 250 delegates, including high-profile political representation. The conference highlighted the need to shift towards further disease integration because of the epidemiological characteristics of the hepatitis B (HBV), hepatitis C (HCV), HIV, sexually transmitted infection (STIs) and tuberculosis (TB) epidemics in the WHO European region. Integration should be a priority in the response to the epidemics to better reach key populations and to ensure better testing coverage. This relates to both the integration of services in shared care models and the integration of different settings and stakeholders in national strategies. Conclusions. The conference demonstrated the need for greater political support for the policy changes required to implement integration. Testing normalization efforts are key to maximizing the impact of integration efforts. The conference call to action can help to guide developments in testing and linkage-to-care interventions across the European region.